Supporting Online Conversations for Students of English as a Foreign Language - Demirci, Fatma (2012)
The purpose of this study is to empirically examine how pictures are used to initiate and support spoken English conversations and how ownership influences these conversations within a Synchronous Computer Mediated Communication environment(SCMC).